INFORMATION-EDUCATIONAL ENVIRONMENT ON PHYSICS AS A MEANS FOR SHAPING SELF-EDUCATIONAL SKILLS OF STUDENTS OF TECHNICAL COLLEGES - T. Semakova (Kherson State University, 2011)
The article examines a structure and functions of the electronic information-educational environment on physics, intended for shaping skills and abilities for self-educational activity of students of technical colleges. Certain methodological recommendations on its use are provided.